KM-QM-technology audit for Universal Colmsen Fashion Center, Inc. - Pagkaliwangan, Joyce Decena (University of the Philippines Diliman, 2012)
Enhancing the organization's performance is the main goal of knowledge management, learning and quality management. An organization championing in these areas will attain sustainable competitive advantage. The modified Knowledge Enabled Excellence in Performance (KEEP) framework was used in this study to further explain the integration of Knowledge Management, Quality Management and Technology to achieve sustainable competitive advantage. The modified Knowledge Enabled Excellence in Performance (KEEP) framework was used in this study to further explain the integration of Knowledge Management, Quality Management and Technology to achieve sustainable competitive advantage. The modified Knowledge Enabled Excellence in Performance (KEEP) framework was used in this study to further explain the integration of Knowledge Management, Quality Management and Technology to achieve sustainable competitive advantage. The modified Knowledge Enabled Excellence in Performance (KEEP) framework was used in this study to further explain the integration of Knowledge Management, Quality Management and Technology to achieve sustainable competitive advantage. Universal Colmsen Fashion Center Inc. has undergone several audits, namely knowledge management, quality management and technology audit, for this study to evaluate the current status of the business and counter check it's alignment to the corporate's vision, mission and core values. The Knowledge management audit explored the areas of the overall environment assessment in knowledge management, perception of knowledge in the organization, the culture of collaboration and sharing, existing knowledge in the workplace, reward system as a motivation and current efforts for continuous improvement. The Quality Management Assessment comprises of an evaluation of the Quality Planning, Quality Control, Quality Assurance and Policy and Standards of the company. The Technology Management Assessment which garnered an average score of 1.94 out of 5 is composed of an audit with regards to the company's technological environment, technological categorization, markets and competitors, innovation process, value-added functions and acquisition and exploitation of technology. The link between market demand/customer satisfaction and quality planning and the technology utilization for Community of Practice (CoP) and Quality Assurance are significant factors that contributed to this study. Overall, the company uses KM and QM practices in their everyday processes. However, the use of technology can be improved more in order to have a result with more valuable impact on the business.